(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this research study we talk about Stress level and coping mechanisms implemented by parents with children with special needs Parenting is a tough exercise and raising a child with disabilities will make it more complicated. Because children with disabilities have disability in physio-psycho-social growth, parents may find their responsibilities rather difficult when coping with behavioral difficulties culminating in social, economicfinancial problems physical and psychological problems reduced quality of life. The challenges associated with cognitive needs of children with disabilities generate uncertainty which parents find unacceptable often at times. The parents with a special child face different set of challenges and needs to follow different coping mechanisms that helps to reduce, change or resolve a traumatic occurrence or crisis scenario. The findings also revealed that engagement coping strategies were often more used in parents, with tendency to use dilemma-based engagement strategies more than emotion-oriented engagement strategies.